Systematic review and meta analysis of mechanical properties of 3D printed denture bases compared to milled and conventional materials - Amr Azab; Walid Awad Abdelhady; Enas Elwakeel; Mohamed Ashraf; Rim Wally; Amir Soliman; Maged Ahmed Mohamed; Dina Abozaid (Scientific Reports)
Abstract Denture base fabrication has advanced with the introduction of computer-aided design and manufacturing (CAD-CAM) techniques, such as subtractive milling and additive 3D printing. However, concerns persist regarding the mechanical performance of 3D-printed denture bases. This systematic review and meta-analysis aimed to evaluate and compare the flexural strength (FS), surface hardness, fracture toughness, and impact strength of 3D-printed denture bases with those produced by milling and conventional methods. A systematic search of PubMed, Scopus, Web of Science, and Cochrane Central was conducted up to March 2025 in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. In vitro studies comparing 3D-printed denture bases with milled or conventional heat-polymerized bases in terms of mechanical properties were included. The Joanna Briggs Institute (JBI) checklist for quasi-experimental studies was used. Data was extracted, and quantitative synthesis was performed where possible. Thirty-eight studies were included, comprising 562 specimens for FS and 231 for surface hardness. Meta-analysis revealed that milled denture bases demonstrated the highest flexural strength (MD = -1.11, 95% CI [-1.29, -0.93], p < 0.001) and surface hardness (MD = -26.49, 95% CI [-29.89, -23.10], p < 0.001) compared to 3D-printed bases. Conventional bases outperformed 3D-printed ones in most mechanical properties. Milled denture bases exhibited the highest FS (120–146 MPa), followed by conventional PMMA (95–119 MPa), while 3D-printed bases showed wider variability (28–128 MPa). Surface hardness (VHN), fracture toughness (MPa·m¹/²), and impact strength (kJ/m²) were also superior in milled bases. Statistical heterogeneity was present due to differences in materials, printing orientation, and post-curing protocols. Subgroup analysis based on printing orientation (0°, 45°, and 90°) partially explained this variability, showing higher FS in horizontally printed specimens. Although 3D-printed denture bases offer customization and production efficiency, their mechanical properties remain inferior to milled alternatives. Optimization of resin formulations, printing parameters, and post-processing protocols is essential to enhance their clinical performance. The main limitations were high heterogeneity among included studies, differences in material formulations, variability in testing standards, and the in vitro nature of most included studies. This review was registered in PROSPERO (CRD420250639092). There were no deviations from the registered protocol.